Sustainable Community Assistance for a Healthy, Responsive, and Disaster-Resilient Tourism Village (Case Study: Sawahan Village, Watulimo District, Trenggalek Regency) - Khambali, Khambali; Rachmaniyah, Rachmaniyah; Fitri Rokhmalia; Yessy Dessy Arna (Frontiers in Community Service and Empowerment, 2025)
Sawahan Village, located in Watulimo District, Trenggalek Regency, is a durian forest tourism area with great potential to be developed as a healthy tourism village. However, the community still faces challenges due to limited knowledge and skills in disaster preparedness and health crisis management. This community service program applied three simultaneous approaches: Communication, Information, and Education (CIE) related to Clean and Healthy Living Behavior (PHBS) in households; assistance in tourism village governance, including administration, financial management, and tourism object development; as well as capacity building for disaster preparedness and resilience. The academic outputs of this program include activity documentation videos and leaflets with Intellectual Property Rights (IPR), a learning module on disaster-resilient tourism villages, and an article submitted to an international journal. Focus Group Discussions (FGDs) revealed that Sawahan Village has strong tourism potential in durian and clove plantations but requires improved facilities and infrastructure. The FGDs and mentoring activities successfully enhanced the competencies of village tourism managers in administration and development, increased community knowledge and skills in PHBS, and strengthened disaster preparedness and health crisis management capacities. Prior to the FGDs, only a small portion of the community understood the importance of tourism village management and healthy living behavior. After the intervention, significant improvements were observed, such as the increase in disaster knowledge from 10% to 84%. This indicates that community service programs can effectively empower rural communities to establish sustainable, healthy, and disaster-resilient tourism villages.